RISK FACTORS IN CHILDREN PRESENTING WITH ACUTE RESPIRATORY INFECTIONS- AN EXPERIENCE AT POF HOSPITAL, WAH CANTT. - Syed Sajid Hussain Shah; Tahir Mehmood; Faiza Sunbleen (Journal of University Medical & Dental College, 2017)
ABSTRACT: BACKGROUND: Acute respiratory infections as pneumonia are one of the leading causes of death in children. OBJECTIVE: This study had been conducted to assess the risk factors causing acute respiratory infections in children below five years of age among the community presenting with pneumonia. DESIGN: Observational study. METHODS: This study was carried out in the Department of Paediatirics, Pakistan Ordnance Factories (POF) Hospital, Wah Cantt from March 2009 till June 2010. All the patients between the ages of three months and five years who were admitted in Paediatric ward of POF Hospital were included in the study. Patients were clerked on a pre-designed proforma. RESULTS: Out of total of 583 patients, 352 (60.4%) were male and 231 (39.6%) were females. The age range was from 3 months to 60 months with mean age of 19.33and SD 15.69. Mostly patients were under age of twenty months. No pneumonia category patients were 251 (43.1%), 270 (46.3%) patients with pneumonia and severe disease and very severe disease 57 (9.8%) and 5 (0.9%) respectively. Vaccinated patients up to date were 564 (96.7%). Family history of atopy was present in 88 (15.1%), carpets and cockroaches exposure in 129 (22.1%) and passive smoking exposure was present in 162 (27.8%) patients. CONCLUSION: As acute respiratory infections lead the morbidity and mortality in young children under five years of age and it requires strategies as vaccination to reduce the burden of disease. By assessment of risk factors and controlling them through public health measures may decrease the incidence of ARI.